Kemahiran Berbahasa Indonesia Siswa Calon Duta Bahasa Pelajar Jabar 2019 Indonesian Language Proficiency of the Candidate of Language Ambassador for Student 2019 in West JavaDi - Samsudin, Dindin (Salingka, 2020)
Duta Bahasa merupakan figur generasi muda yang bertugas mengampanyekan dan menyosialisasikan penggunaan bahasa Indonesia yang baik dan benar. Seorang Duta Bahasa tentu  harus memiliki kemahiran berbahasa Indonesia yang baik agar dapat memberikan contoh penggunaan bahasa Indonesia secara tepat. Di samping itu, sebagai seorang siswa juga harus memiliki kemahiran berbahasa Indonesia yang baik agar pengajaran  yang diberikan oleh guru dapat diterima dengan baik. Penelitian ini bertujuan  untuk mengungkapkan kemahiran berbahasa Indonesia para siswa calon Duta Bahasa Jabar tahun 2019. Metode deskriptif kualitatif digunakan untuk mendeskripsikan dan menganalisis data yang bersumber dari rekapitulasi skor UKBI peserta calon Duta Bahasa Jabar Tahun 2019. Hasil dari penelitian ini menunjukkan bahwa secara rata-rata siswa calon Duta Bahasa Jawa Barat memiliki predikat kemahiran berbahasa Indonesia peringkat “Unggul”dalam kemahiran berbahasa Indonesia. Berdasarkan hal tersebut, secara rata-rata, para siswa calon Duta Bahasa Jabar tahun 2019 memenuhi standar kemahiran berbahasa Indonesia bagi profesi pelajar SLTA.The Language Ambassador is a figure of the young generation who has duties to campaign and socialize the use of Indonesian language correctly and well. A language ambassador must have good skills in the Indonesian language to give examples of the right use of the Indonesian language. Besides, a student must also have a good Indonesian language proficiency so that the teaching given by the teacher can be well received. This study aims to find out the Indonesian language proficiency of the candidate of language ambassador for student 2019 in West Java. The descriptive qualitative method was used to describe and analyze the data that sourced from the recapitulation scores of the Indonesian Language Proficiency Test (UKBI) of the participants of language ambassador candidates for student 2019 in West Java. The result of this study shows that on average the candidate of language ambassador for the student has Good (Unggul) predicate in the Indonesian language proficiency level. Based on that fact, the average of the candidate of language ambassador for student 2019 in West Jawa has met the standard of Indonesian language proficiency for the profession of high school students.